Komunikasi Interpersonal pada Pasangan Suami-Istri Remaja Pasca Pernikahan Ta’aruf : Studi Fenomenologi komunikasi interpersonal istri pada suami yang Menikah melalui Ta’aruf di Bandung - Sheilla Syania Tholib; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. The word ta'aruf has the meaning of getting acquainted and in the concept of marriage ta'aruf is that in the introduction process before marriage is brokered by a third party and even the couples only meet a few times so that they proceed to marriage. Therefore, this thesis has the aim of knowing the interpersonal communication of wives to husbands who are married through the ta'aruf process by examining the motives, experiences and also the meaning of ta'aruf marriage by using a qualitative approach with phenomenological methods in solving research and using Alfred Schutz's phenomenological theory. , social penetration and Uncertainty Reduction as a reference in this issue. This research was conducted by observation and literature study, the object of which came directly from the field using the snowball sampling technique not in a specific place but spread out. The results of the study show that there are three motives, namely past motives (the process of hijrah, religious orders, motives due to self-indulgence and belief motives), the present (communication after marriage is more open to understanding each other and having a vision and mission of the future) and the future (the motive of the desire for a harmonious family, the motive for getting a partner who understands religion, the motive for having religiously devout offspring). Experience before marriage (early phase, personal phase and final phase). Post-marital communication experience in the process of togetherness with couples (Initiating, Experimenting, Intensifying, Integrating, Bonding) Interpersonal communication process of ta'aruf couples in developing relationships with (affection, control and Infusion). The meaning of ta'aruf marriage has three general meanings, namely the process towards marriage according to Islamic law, marriage by submitting to Allah's arrangements and the process before marriage that does not involve disobedience. Abstrak. Kata ta’aruf memiliki makna berkenalan dan pada konsep pernikahan ta’aruf adalah yang pada proses perkenalan sebelum pernikahan diperantai oleh pihak ketiga dan bahkan para pasangan hanya bertemu beberapa kali sehingga lanjut ke pernikahan. Maka dari itu Skripsi ini mempunyai tujuan untuk mengetahui komunikasi interpersonal Istri pada Suami yang menikah melalui proses ta’aruf dengan mengkaji motif, pengalaman dan juga makna dari pernikahan ta’aruf dengan menggunakan pendekatan kualitatif dengan metode fenomenologi dalam memecahkan penelitiannya dan menggunakan teori fenomenologi Alfred Schutz, penetrasi sosial dan Uncertainty Reduction sebagai acuan dalam masalah ini. Penelitian ini dilakukan dengan observasi dan studi pustaka, yang obyeknya langsung berasal dari lapangan dengan menggunakan Teknik snowball sampling tidak di tempat yang spesifik namun tersebar. Hasil penelitian menunjukan adanya tiga motif yaitu motif masa lalu (proses hijrah, perintah agama, motif karena dorongan dari diri dan motif keyakinan) , masa kini (komunikasi setelah pernikahaan lebih terbuka saling memahami dan memiliki visi misi kedepan ) dan masa yang akan datang (motif keinginan keluarga harmonis,motif mendapat pasangan yang paham agama, motif mempunyai keturunan yang taat agama). Pengalaman sebelum pernikahaan (fase awal , fase personal dan fase akhir). Pengalaman komunikasi pasca pernikahan dalam proses kebersamaan pasangan dengan (Initiating,Experimenting, Intensifying, Integrating,Bonding) Proses komunikasi Interpersonal pasangan ta’aruf dalam pengembangan hubungan dengan (afeksi,kontrol dan Influsi ). Makna dari pernikahaan ta’aruf mempunyai tiga makna umum yaitu Proses menuju pernikahan yang sesuai syariat islam, Pernikahaan dengan menyerahkan pada pengaturan Allah dan Proses sebelum pernikahaan yang tidak melibatkan kemaksiatan.